Progress in The Study of Land Use Landscape Patterns - Xia, Liheng; Zhang, Fang (International Journal of Natural Resources and Environmental Studies, 2024)
Landscape pattern refers to the spatial distribution and configuration of heterogeneous geographic units composed of different ecosystems, i.e., landscape elements, and is usually determined by the type, number, scale, shape and spatial distribution pattern of landscape elements. The formation of landscape patterns is mostly the result of complex interactions among physical, biological and socio-economic factors. Land use change (LUCC) is one of the key factors affecting the structure, function and dynamics of landscapes, and LUCC can not only objectively reflect the use of natural resources such as land and potential ecological risks by human activities, but also reveal the mechanisms of interaction between human activities and the ecological environment.